Pengaruh Struktur Modal Terhadap Net Profit Margin Pada PT Astra Internasional Tbk yang Terdaftar di Bursa Efek Indonesia 2021-2023 - Harianti Harianti; Aisyah Syahrir; Muhammad Arya Maulana; Nurhikma Nurhikma; Kasma Kasma (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2025)
This study aims to analyze the effect of the Debt to Equity Ratio (DER) on the Net Profit Margin (NPM) of PT Astra International Tbk, listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. This research employs a descriptive quantitative approach using secondary data obtained from the company's annual financial reports. Data analysis techniques include descriptive analysis, Pearson correlation test, and simple linear regression. The results show a negative relationship between DER and NPM, with a correlation coefficient of -0.726, indicating that an increase in DER tends to be followed by a decrease in NPM. However, this relationship is not statistically significant, with a p-value of 0.483. Regression analysis results reveal that DER can only explain 52.7% of the variation in NPM, while the remaining percentage is influenced by other variables outside this research model. Therefore, although capital structure plays a role in influencing profitability, other factors such as operational efficiency and cost management also need to be considered to improve the company's financial performance.